Food and Agriculture Policy in Europe - Christopher A Birt (AIMS Press, 2016)
Diet includes many risk factors for the most common non-communicable diseases (NCDs), but diets consumed in Europe and in other parts of the developed world are not being modified sufficiently to take account of health priorities concerning, in particular, the prevention of NCDs, while much excess mortality and morbidity could be prevented by government actions to regulate appropriately both the agricultural and food industries, and to apply appropriate taxes and subsidies to promote healthier nutrition. In Europe, the Common Agricultural Policy (CAP) continues to promote production of saturated fat rich foods and sugar, with scarce attempts to promote increased production of fruit and vegetables. Meanwhile, the food industry continues to market secondary food products rich in sugar, salt and saturated fats. Powerful lobbies seek to block reform; however, necessary reforms are indicated in the interests of improved nutritional health.